Optimasi Rencana Tanam dan Pemberian Air Irigasi menuju Modernisasi Irigasi di Daerah Irigasi Ciliman - - Susilowati; Widya Utaminingsih; Segel Ginting (Jurnal Irigasi, 2020)
Development of an irrigation area were implemented to increase the productivity of agricultural products, especially rice and palawija (secondary crops commodities). The productivity of rice and palawija was influenced by irrigation performance, both by infrastructure and irrigation management. The operation management of irrigation network in Ciliman Irrigation Area is still not optimal due to the absence of an operations to regulate the amount of water that enters each tertiary intake causing excessive water intake upstream while shortage in the downstream. This is also exacerbated by the condition of water availability in the dry season which is lower compared to the need of irrigation water. Therefore, this research is conducted to optimize the cropping pattern and water allocation in Ciliman Irrigation Area by considering the reliability of irrigation water delivery. Research was conducted through water balance simulation according to several scenarios based on group division, changes in the planting schedules, and changes in planting area. Then, optimization of the cropping pattern was done by maximizing the reliability of irrigation water delivery. The recommended cropping pattern is 100% rice planted in planting season I, 100% rice planted in planting season II, and 27.47% palawija (soybean) planted in planting season III. Water delivery should be arranged into 3 groups with the 1st planting schedule starts in 1st period of November, 2nd planting season starts in 1st period of March, and 3rd planting season starts in 2nd period of July. With this scenario, there was an increase in the cropping index from the existing conditon of 199.7 (83% reliability) to 213.7 (100% reliability).